2014
DOI: 10.1002/mabi.201300580
|View full text |Cite
|
Sign up to set email alerts
|

Sequential pH‐Dependent Adsorption of Ionic Amphiphilic Diblock Copolymer Micelles and Choline Oxidase Onto Conductive Substrates: Toward the Design of Biosensors

Abstract: This work examines the fabrication regime and the properties of polymer-enzyme thin-films adsorbed onto conductive substrates (graphite or gold). The films are formed via two-steps, sequential adsorption of poly(n-butylmethacrylate)-block-poly(N,N-dimethylaminoethyl methacrylate) (PnBMA-b-PDMAEMA) diblock copolymer micelles (1st step of adsorption), followed by the enzyme choline oxidase (ChO) (2nd step of adsorption). The solution properties of both adsorbed components are studied and the pH-dependent step-by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 62 publications
4
23
0
3
Order By: Relevance
“…It is worth noting that the degree of protonation of the PDMAEMA block of 25 – 30% at physiological pH of 7.4 (see potentiometric titration curves given in the Figure S4 ) was sufficient for the strong multipoint anchoring of DNA. This corresponds to the results we already reported for the pH-dependent interaction of similar diblock copolymers deposited onto solid surfaces with enzymes and proteins [ 35 , 40 , 42 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It is worth noting that the degree of protonation of the PDMAEMA block of 25 – 30% at physiological pH of 7.4 (see potentiometric titration curves given in the Figure S4 ) was sufficient for the strong multipoint anchoring of DNA. This corresponds to the results we already reported for the pH-dependent interaction of similar diblock copolymers deposited onto solid surfaces with enzymes and proteins [ 35 , 40 , 42 ].…”
Section: Resultssupporting
confidence: 91%
“…The typical appearance of the micelles is shown in Figure S3 . The solution behavior of P n BMA x - b -PDMAEMA y diblock copolymers is in good agreement with former published data for similar diblock copolymers [ 40 ].…”
Section: Resultssupporting
confidence: 90%
“…This graphite-based surface is characterized by high roughness due to the presence of 3–10 μm graphite flakes, with the roughness within one flake being 86 ± 2 nm [6,12]. The high hydrophobicity of this surface results in a hard wettability, confirmed by the high value of the static contact angle of 133.3° ± 0.8°, to which a high roughness makes an additional contribution [5,6]. The initial graphite surface was additionally premodified with MnO 2 nanoparticles to impart the surface sensitivity to hydrogen peroxide (see Experimental Part, and the Scheme 2 therein).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have shown that the surface modification of conductive substrates by functional polymers via their simple adsorption under the right conditions allows for the subsequent efficient binding of biomolecules, where the polymer layer acts as peculiar ‘glue’ keeping such bioactive species firmly at the interface [5,6]. With the help of this approach, easily-preparable enzymatic biosensor setups were constructed and applied for electrochemical detection of choline [5,6,7,8], phenol [5,9,10], blood esterases [9,11], and organophosphates [12].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer membrane based biosensors have been applied in fluids, as detecting surfaces, and in the form of immobilized nanoreactors on functionalized surfaces (Turner, 2013). For example, micelles of poly (n-butylmethacrylate)-block-poly (N,N-dimethylaminoethyl methacrylate) (PnBMA- b -PDMAEMA), and choline oxidase were used to obtain bilayer films on conductive surfaces at different pH-values (Sigolaeva et al, 2014). Sequential electrostatic adsorption of diblock copolymer micelles combined with the additional possibility of crosslinking enzymes within such films produced highly active and stable biosensor coatings.…”
Section: Present and Future Perspectives On Biomedical Applicationsmentioning
confidence: 99%